Voluntary environmental standards, Nationally Appropriate Mitigation Actions and the Green Deal: Elements for discussion in the case of the coffee sector - Arce Alvarado, Randall (2024)
The increased voluntary environmental standards in coffee production have been a relevant issue, especially in sustainability and global value chain behavior. Likewise, measures such as Nationally Appropriate Mitigation Actions (NAMA) and the European Union's Green Deal influence this sector. Through a literature review, this article analyzes the interrelations between voluntary standards, NAMA, and the potential to comply with Green Deal requirements, as well as the impact on the productive sector. Standards can contribute to sustainable development goals and emissions reduction, but they are not the ultimate solution to improve the conditions of primary producers. From a market access perspective, productive organizations that have applied sustainability standards and countries with NAMA strategies for the coffee sector are better prepared to comply with the Green Deal. However, the need for public policies to support the sectors, the generation of adequate financing mechanisms, and prospective studies to improve the positioning in the value chains continue to be necessary elements of action that must be strengthened in the short and medium term. Finally, there is still pending conciliation within the World Trade Organization on how these measures will be incorporated into its operating structure.